Football Performance Test - Vincenzo Alberto Annese; Tandiyo Rahayu; Soegiyanto MS; Donny Wira Yudha Kusuma (Universitas Negeri Semarang, 2022)
This research on the professional football coach competency evaluation instrument was done because there was no existing instrument used to measure the test to select players’ competence in India (female and male). Subjects in this study, 18 male and 18 female players from India from a professional sports club were involved respectively. The physical characteristics of the participants are shown in this experimental study. The players performed a battery of four tests during normal weekly training. The research was in the period between January and March 2022 in quantitative method research. Motor capacity in detail, the speed was analyzed with a 20 m Sprint, the strength with a counter-movement without using the arms (CMJ), the resistance with the